Degradation of Acid Red 18 by Fenton Reagent Combined with UV - Liyong, Wang; Yuanyuan, Han; Lanfen, Li (Asian Journal of Chemistry, 2010)
Degradation of acid red 18 (AR18) by mean of Fenton reagent (FR) combinated with UV was investigated for a variety of operating conditions. It is found that the degradation rate of acid red 18 is dependent on the pH value, the Fe2+ and H2O2 dosage and the initial concentration of the dye. Under the given test conditions, 99.6 % degradation efficiency was achived after 0.5 h reaction by Fenton reagent combined with UV (UV/FR). The results show that the UV/FR can be an effective technology for the treatment of azo dyes in wastewater.